Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 26. Beitrag: Coleoptera: Malachiidae. - Evers, Alfons Maria Johannes; Friese, Gerrit (Contributions to Entomology = Beiträge zur Entomologie, 1964)
The expedition of the Deutsches Entomologisches Institut collected 175 specimens of the Coleopterous family Malachiidae. They belong to 15 species, 8 of which are new to the fauna of Albania. 2 of these species, Charopus rotundatus Erichson and Malachius dissimilis Baudi, are new to the Balkan countries. Up to now there are kown 28 species of Malachiidae from Albania. There is described a nov. var. of Malachius dilaticornis Germar.Nomenclatural Actsdilaticornis immaculatus Evers, 1964 (Malachius), ssp. nov.